(untitled) (Actualizaciones en Sida e Infectología, 2025)
Whiple Disease (WD), caused by Tropheryma whipplei, is a rare, multisystem disease (infection?) that mainly affects immunocompromised patients, such as people with human immunodeficiency virus (HIV). We are reported a 42-year-old patient with HIV and WD who presents chronic diarrhea, severe weight loss, and multisystemic symptoms. The diagnosis is confirmed by biopsy and PCR, showing gastrointestinal and central nervous system involvement. Treatment included intravenous ceftriaxone followed by trimethoprim-sulfamethoxazole, along (as well) with antiretroviral therapy. A gradual clinical recovery was achieved with resolution of diarrhea and weight gain. This case highlights the challenges of managing coinfections in immunocompromised patients and the importance of comprehensive diagnosis, endoscopic follow-up, and combination therapies to optimize the management of these complex conditions.